Analytical and Numerical Studies of an Unsymmetrical Sandwich Beam – Bending, Buckling and Free Vibration - MAGNUCKI, Krzysztof; MAGNUCKA-BLANDZI, Ewa; LEWIŃSKI, Jerzy; MILECKI, Szymon (Engineering Transactions, 2019)
The subject of the paper is an unsymmetrical sandwich beam. The thicknesses and mechanical properties of the beam faces are different. Mathematical model of the beam is formulated based on the classical broken-line hypothesis. The equations of motions of the beam is derived on the ground of the Hamilton’s principle. Bending, buckling and free-vibration are studied in detail for exemplary unsymmetrical structure of the beam. The values of deflection, critical force and natural frequency are determined for the selected beam cases. Moreover, the same examples are computed with the use of two FEM systems, i.e. SolidWorks and ABAQUS, in order to compare the analytical and numerical calculation. The results are presented in Tables and Figures.